2011
DOI: 10.1016/j.rmed.2011.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Th17 cells in peripheral blood of patients with chronic obstructive pulmonary disease

Abstract: The increase of Th17 response and the lost of balance between CD4(+) T cell subsets, suggest a lack of regulation of the systemic inflammatory response that may contribute to pathogenesis in COPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
4
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 39 publications
11
100
4
9
Order By: Relevance
“…The influence of smoke on leukocyte cell numbers and cell function has been demonstrated in several previous studies and our results are consistent with these findings [9,[32][33][34][35]. On the contrary, data concerning the influence of smoking on lymphocyte subpopulations are conflicting [35][36][37][38]. This may be due to the age of the population recruited, smoking habits, healthy status, etc.…”
Section: Variablessupporting
confidence: 91%
See 1 more Smart Citation
“…The influence of smoke on leukocyte cell numbers and cell function has been demonstrated in several previous studies and our results are consistent with these findings [9,[32][33][34][35]. On the contrary, data concerning the influence of smoking on lymphocyte subpopulations are conflicting [35][36][37][38]. This may be due to the age of the population recruited, smoking habits, healthy status, etc.…”
Section: Variablessupporting
confidence: 91%
“…Changes in lymphocyte subpopulations may reflect progressive changes from non-smokers to healthy smokers to patients with COPD. Very interesting are the data reported by Vargas-Rojas and collaborators showing a polarisation of Th17 cells and their balance with Th1/Th2 and Treg subpopulations in COPD and current smokers, with Th17 and Treg cells showing a progressive increase from healthy subjects to current smokers to COPD group [38].…”
Section: Variablesmentioning
confidence: 95%
“…42,43 The function of Th17 in COPD is less known; an enhancement of Th17 differentiation was observed in peripheral blood and bronchial biopsies of COPD patients compared to those of healthy control. 44,45 We found that CD4 T cells in sγcTg mice were much more skewed to Th17 compared to WT mice with CSE treatment, indicating that more IL-17 production from increased Th17 cell differentiation may recruit more inflammatory responsible cells in COPD. Indeed, IL-17 may induce chemokine secretion [46][47][48] and promote the infiltration of neutrophils and macrophages to peripheral airway.…”
Section: Discussionmentioning
confidence: 85%
“…Además, en los pacientes con EPOC grave se ha observado una alta expresión de IL-18, citoquina que promueve el desarrollo de las células Th1 74 . En cuanto a las células Th17, las cuales están implicadas en procesos autoinmunes y en el reclutamiento de otras células inflamatorias a tejidos 75 , se encuentran incrementadas en sangre de enfermos de EPOC en comparación a fumadores control 76 . Por otro lado, también se ha reportado un incremento de células que expresan IL-17A (una de las principales interleuquinas producidas por las células Th17) en submucosa de pacientes con EPOC 72 .…”
Section: Los Linfocitos T Cd4unclassified